A kind of aniline pyridine amino-aluminum catalyst and its preparation method and application
By designing and synthesizing aniline pyridine amino-aluminum ((AmPyPh)AlMe) catalyst, the problem of lack of high heat stability and proton resistance catalysts in the prior art is solved, and the ring-opening polymerization of L-LA, ε-CL and δ-VL is efficiently catalyzed under industrial conditions, and the resulting polylactic acid has high molecular weight and low molecular weight distribution.
Patent Information
- Application Number
- CN202411185260.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-27
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-08-27
AI Technical Summary
The lack of catalysts with high heat stability and proton resistance in the prior art makes it difficult to efficiently catalyze the ring-opening polymerization of L-LA, ε-CL and δ-VL under industrial conditions, resulting in unsatisfactory molecular weight and distribution of polylactic acid.
Anilinylpyridine amino-aluminum ((AmPyPh)AlMe) catalyst was designed and synthesized. This catalyst was prepared by reacting with an aluminum source, with high activity, good heat resistance and impurity resistance, and was able to efficiently catalyze the ring-opening polymerization of L-LA, ε-CL and δ-VL under 150°C.
The ring-opening polymerization of L-LA, ε-CL and δ-VL is achieved under industrial-related conditions. The resulting polylactic acid has high molecular weight and low molecular weight distribution, and the low biotoxicity and high activity of the catalyst have application prospects.
Smart Images

Figure CN118878459B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polyester catalysts, and in particular relates to an aniline pyridine amino-aluminum catalyst and a preparation method and application thereof. Background Art
[0002] Plastics have become an indispensable substance in human daily life. The natural degradation process of traditional petroleum-based plastics (such as polyolefins) is extremely slow, which has caused serious "white pollution". Microplastics produced by the decomposition of petroleum-based plastics will diffuse and enrich in the food chain, while landfilling and incineration of petroleum-based plastics will cause more serious secondary pollution. Therefore, sustainable and fully degradable bio-based plastics are increasingly attracting attention from academia and industry. Aliphatic polyesters (such as polylactic acid (PLA), polycaprolactone (PCL), etc.) are currently the most widely used environmentally friendly degradable polymer materials. Due to its good mechanical properties and easy processing, PLA is often used in food packaging, disposable tableware, medical supplies, textiles and other fields. At the same time, PLA can be decomposed into water and carbon dioxide in industrial composting, and it will degrade into lactic acid in the body in just a few weeks; PCL and PVL can be used as cell growth support materials, and can be completely degraded in 6-12 months under natural conditions. Its good shape memory temperature control properties are often used as carriers for drug release. Although aliphatic polyesters are slightly inferior to some traditional plastics in terms of heat resistance and rigidity, they perform well in terms of transparency, glossiness, biocompatibility, etc., and have many advantages over traditional petrochemical-derived plastics, and have a very broad market prospect.
[0003] Ring-opening polymerization of L-lactide (L-LA), ε-caprolactone (ε-CL), and δ-valerolactone (δ-VL) is an effective method for the production of high molecular weight polyesters from renewable monomers, whose mechanical, thermal, and degradation properties can be largely tuned by the catalyst system. PLA, PCL, and PVL can be produced on an industrial scale at high temperatures (140-200 °C) and in the absence of solvents (melt). Di(2-ethylhexanoate)tin [Sn(Oct)2] is the main industrial catalyst for the production of PLA, PCL, and PVL, thanks to its low cost, few side reactions, high impurity tolerance, and high activity. In addition, the white polymer produced by Sn(Oct)2 catalysis does not require decolorization. However, Sn(Oct)2 is highly toxic to humans, and its accumulation and residue in the environment and human body must be of concern, so industrial production requires additional purification of the polymer to remove the toxic residual tin. Therefore, it is highly desirable to develop benign alternative catalysts that are compatible with existing infrastructure and suitable for the production of polylactic acid under industrial conditions.
[0004] Low / non-toxic metals (e.g., magnesium, aluminum, zinc, and iron) have been used for the polymerization of the above monomers over the past few decades. Aluminum-based complexes have received particular attention due to the high Lewis acidity and natural abundance of aluminum. Although aluminum-based catalysts are highly active in the polymerization of ε-CL, they only show low and moderate activity in the ROP of L-LA. In addition, most of these catalysts are usually used for solution polymerization at 25-100 °C, and only a few can be used for solvent-free polymerization at high temperatures (e.g., 150-180 °C). Salen aluminum complexes can promote the stereoselective polymerization of rac-LA under solvent-free conditions. However, the high loading of the catalyst ([Al]>0.3 mol%) severely limits its potential application in the commercial production of high-performance polylactic acid. The latest study by Romain et al. has overcome this limitation to some extent. They reported that chiral Catam aluminum-based complexes showed extremely high activity, polymerizing 9,200 equivalents of L-LA in 4.5 minutes at 150 °C, but the molecular weight of the polymerized PLLA was only about 10 KDa. Therefore, there is still a lack of highly thermally stable and proton-resistant catalysts for industrial polylactic acid production. Summary of the invention
[0005] In order to solve the above technical problems, the present invention proposes an aniline pyridine amino-aluminum catalyst and its preparation method and application. The aniline pyridine amino-aluminum catalyst of the present invention can efficiently catalyze the ring-opening polymerization of L-LA, ε-CL and δ-VL into high molecular weight and low molecular weight distribution PLA, PCL and PVL polyesters.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] One of the technical solutions of the present invention:
[0008] An anilinopyridine amino (AmPyPh) ligand, the structure of which is shown in Formula I:
[0009]
[0010] Among them, the X group is F, t-Bu or OCH3, the R group is Ph, CH3 or CH(CH3)2, the Z group is H or CH(CH3)2, and the Y group is F, H or OCH3.
[0011] Preferably, the AmPyPh ligand is selected from compounds of LA to LI structures:
[0012]
[0013] The second technical solution of the present invention:
[0014] A method for preparing the AmPyPh ligand comprises the following steps:
[0015] 2-(tert-butyl)-4-X-6-(4,4,5,5-tetramethyl-1,3-dioxaboryl)phenol with different X substituents (purchased from WuXi AppTec, used directly without purification) was selected, and it and 6-bromopyridine-2-carboxaldehyde were added to a branched flask successively, and then methanol and saturated sodium carbonate solution were added; after connecting a reflux device and evacuating the suspension to remove dissolved oxygen, nitrogen was introduced, and a toluene solution of tetrakis(triphenylphosphine palladium) (Pd(PPh3)4) was added to carry out a coupling reaction, and after the reaction was completed, ethyl acetate was used for extraction, and the liquid was separated after standing, and the upper oil phase was taken, dried over anhydrous magnesium sulfate, and then rotary evaporated to obtain a crude product, which was purified by column chromatography to obtain the first step product;
[0016] After obtaining the first step product, fully dissolve it in methanol, add substituted or unsubstituted aniline, and carry out Mannich reaction under acid catalysis. After the reaction is completed, filter and rinse with methanol for purification to obtain the second step product;
[0017] Add the fully dried product of the second step into a branched flask, connect an anhydrous and oxygen-free device, add a solvent into the branched flask, place the branched flask in a low-temperature environment of -78°C, add 2 equivalents of lithium source solution with different substituents, stir evenly, and react at room temperature for 12 to 24 hours, preferably 15 hours; after the reaction, add saturated ammonium chloride aqueous solution for quenching, extract with ethyl acetate, stand and separate the liquids, take the upper oil phase and dry it with anhydrous magnesium sulfate, finally rotary evaporate to obtain a crude product, purify it with column chromatography, and finally recrystallize it with methanol to obtain the AmPyPh ligand.
[0018] Preferably, in the preparation method of the AmPyPh ligand, when the coupling reaction is carried out, the reaction temperature is 110-130°C and the reaction time is 13-24h, more preferably the reaction temperature is 130°C and the reaction time is 20h;
[0019] The equivalent ratio of the first step product to the substituted or unsubstituted aniline is 1:1.5;
[0020] The acid is formic acid or p-toluenesulfonic acid, more preferably p-toluenesulfonic acid;
[0021] When the Mannich reaction is carried out, the reaction temperature is 25 to 50°C and the reaction time is 13 to 24 hours, more preferably the reaction temperature is 40°C and the reaction time is 24 hours;
[0022] The water-free and oxygen-free device is preferably a double-row tube;
[0023] The solvent is anhydrous and oxygen-free ethyl ether, anhydrous and oxygen-free tetrahydrofuran or anhydrous and oxygen-free 1,4-dioxane, and more preferably the solvent is anhydrous and oxygen-free ethyl ether.
[0024] Preferably, in the method for preparing the AmPyPh ligand, the substituted or unsubstituted aniline is 2,6-diisopropylaniline, 4-fluoroaniline, aniline or 4-methoxyaniline.
[0025] Preferably, in the method for preparing the AmPyPh ligand, the lithium source solution with different substituents is a phenyllithium solution, a methyllithium solution, an isopropyllithium solution or a lithium aluminum hydride solution.
[0026] Preferably, in the preparation method of the AmPyPh ligand, the column chromatography purification adopts PE / EA (petroleum ether / ethyl acetate) phase for elution.
[0027] The third technical solution of the present invention:
[0028] The present invention also provides an aniline pyridine amino-aluminum ((AmPyPh)AlMe) catalyst, which is prepared from the above-mentioned AmPyPh ligand, and the structural formula of the (AmPyPh)AlMe catalyst is as follows:
[0029]
[0030] Among them, the X group is F, t-Bu or OCH3, the R group is Ph, CH3 or CH(CH3)2, the Z group is H or CH(CH3)2, and the Y group is F, H or OCH3.
[0031] Preferably, the (AmPyPh)AlMe catalyst is selected from a complex having an Al1-Al9 structure:
[0032]
[0033] The fourth technical solution of the present invention:
[0034] The present invention also provides a method for preparing the (AmPyPh)AlMe catalyst, comprising the following steps:
[0035] The AmPyPh ligand is dissolved in a pressure bottle filled with a good solvent, an aluminum source is added dropwise, and the bottle is sealed and heated to 100-105° C. for reaction. The reaction time is 16-30 hours. After the reaction is completed, the solvent is drained and recrystallized using ultra-dry n-hexane to obtain the (AmPyPh)AlMe catalyst.
[0036] Preferably, in the preparation method of the (AmPyPh)AlMe catalyst, the aluminum source is trimethylaluminum (AlMe3); the good solvent for dissolving the AmPyPh ligand is tetrahydrofuran, dichloromethane or toluene, more preferably toluene; the good solvent for dissolving the aluminum source is toluene or n-hexane, more preferably n-hexane.
[0037] The fifth technical solution of the present invention:
[0038] The present invention also provides the use of the (AmPyPh)AlMe catalyst in catalyzing the ring-opening polymerization of lactide and / or lactone.
[0039] Technical solution six of the present invention:
[0040] The present invention also provides a method for catalyzing the ring-opening polymerization of lactide and / or lactone using the above-mentioned (AmPyPh)AlMe catalyst, comprising the following steps: mixing lactide and / or lactone monomers, (AmPyPh)AlMe catalyst and initiator, carrying out polymerization reaction at a temperature of 150-160°C, dissolving the obtained polymer after the polymerization is completed, reverse precipitation and then drying.
[0041] Preferably, in the method of catalyzing the ring-opening polymerization of lactide and / or lactone using the above-mentioned (AmPyPh)AlMe catalyst, the monomer is L-lactide (L-LA) or rac-LA obtained after recrystallization purification, ε-caprolactone (ε-CL) and δ-valerolactone (δ-VL) obtained after distillation purification, and the above-mentioned monomers are free of water and other impurities.
[0042] Preferably, in the method of catalyzing the ring-opening polymerization of lactide and / or lactone using the above-mentioned (AmPyPh)AlMe catalyst, the initiator is benzyl alcohol (BnOH) or 1,4-butanediol (BDO).
[0043] Preferably, in the method of catalyzing the ring-opening polymerization of lactide and / or lactone using the above-mentioned (AmPyPh)AlMe catalyst, the solvent for dissolving the polymer is dichloromethane or chloroform; the equivalent ratio of the initiator to the monomer is 0.001 and the equivalent ratio of the (AmPyPh)AlMe catalyst to the monomer is 0.001-0.01.
[0044] Preferably, in the method of catalyzing the ring-opening polymerization of lactide and / or lactone using the above-mentioned (AmPyPh)AlMe catalyst, the polymerization reaction time is 0.01 to 48 hours, more preferably 12 to 30 hours.
[0045] More preferably, in the method of catalyzing the ring-opening polymerization of lactide and / or lactone using the above-mentioned (AmPyPh)AlMe catalyst, the polymerization reaction temperature is 150° C. and the time is 12 hours.
[0046] More preferably, the present invention utilizes the above-mentioned (AmPyPh)AlMe catalyst having the structure of formula Al1~Al9 to synthesize aliphatic polyester (PLLA) having the structure of formula II-1.
[0047]
[0048] The specific method is: using bulk or solution polymerization, at a certain polymerization temperature, the (AmPyPh)AlMe catalyst with the structure of formula Al1~Al9 initiates the ring opening and polymerization of the monomer L-LA. After a certain reaction time, the obtained polymer is dissolved, reversed, filtered, and dried to obtain PLLA with the structure of formula II-1.
[0049] Preferably, in the above method, the polymerization temperature is 100-160°C.
[0050] Preferably, in the above method, the initiator is benzyl alcohol or BDO (1,4-butanediol).
[0051] Preferably, in the above method, the polymerization time is 0.01 to 48 hours, more preferably 6 to 12 hours.
[0052] Preferably, in the above method, the solvent used to dissolve the polymer is dichloromethane.
[0053] Preferably, in the above method, the molar ratio of the (AmPyPh)AlMe catalyst having a structure of formula Al1 to Al9, the initiator, and the monomer L-LA is 1:1:(100 to 20000).
[0054] Preferably, in the method for preparing aliphatic polyester having the structure of formula II-1, the conversion rate of monomers into polyester is greater than 96%.
[0055] In the present invention, aliphatic polyester (PLA) having a structure of formula II-2 is synthesized using the above-mentioned (AmPyPh)AlMe catalyst having a structure of formula Al1 to Al9.
[0056]
[0057] The specific method is: using bulk polymerization, with benzyl alcohol as the initiator and a certain polymerization temperature, the (AmPyPh)AlMe catalyst with the structure of formula Al1~Al9 initiates the ring opening and polymerization of the monomer rac-LA. After a certain reaction time, the obtained polymer is dissolved, reversed, filtered, and dried to obtain an aliphatic polyester (PLA) with the structure of formula II-2.
[0058] Preferably, in the above method, the polymerization temperature is 130-160°C;
[0059] Preferably, in the above method, the polymerization time is 0.01 to 48 hours, more preferably 12 to 48 hours;
[0060] Preferably, in the above method, the solvent used to dissolve the polymer is dichloromethane;
[0061] Preferably, in the above method, the molar ratio of the (AmPyPh)AlMe catalyst having a structure of formula Al1 to Al9, the initiator and the monomer rac-LA is 1:1:1000;
[0062] Preferably, in the method for preparing aliphatic polyester having the structure of formula II-2, the conversion rate of monomer to polyester is greater than 99%.
[0063] In the present invention, aliphatic polyester (PCL) having a structure of formula III is synthesized using the (AmPyPh)AlMe catalyst having a structure of formula Al1 to Al9.
[0064]
[0065] The specific method is: using bulk or solution polymerization, with benzyl alcohol as an initiator and a certain polymerization temperature, the (AmPyPh)AlMe catalyst with the structure of formula Al1~Al9 initiates the ring opening and polymerization of the monomer ε-CL. After a certain reaction time, the obtained polymer is dissolved, reversed, filtered, and dried to obtain an aliphatic polyester (PCL) with the structure of formula III.
[0066] Preferably, in the above method, the polymerization temperature is 100 to 150°C;
[0067] Preferably, in the above method, the polymerization time is 0.01 to 48 hours;
[0068] Preferably, in the above method, the solvent used to dissolve the polymer is dichloromethane;
[0069] Preferably, in the above method, the molar ratio of the (AmPyPh)AlMe catalyst having a structure of formula Al1 to Al9, the initiator and the monomer ε-CL is 1:1:(100 to 1000);
[0070] Preferably, in the aliphatic polyester having the structure of formula III, the conversion rate of the monomer into polyester is greater than 99%.
[0071] In the present invention, the unsaturated polyester having the structure of formula IV is synthesized by using the catalyst having the structure of formulas A1 to A19.
[0072]
[0073] The specific method is: using bulk or solution polymerization, with benzyl alcohol as an initiator and a certain polymerization temperature, a catalyst with a structure of formula Al1 to Al9 initiates the ring opening and polymerization of the monomer δ-VL, after a certain reaction time, dissolving, reverse precipitation, filtering, and drying the obtained polymer to obtain an unsaturated polyester with a structure of formula IV.
[0074] Preferably, in the above method, the polymerization temperature is 100 to 150°C;
[0075] Preferably, in the above method, the polymerization time is 0.01 to 48 hours;
[0076] Preferably, in the above method, the solvent used to dissolve the polymer is dichloromethane;
[0077] Preferably, in the above method, the molar ratio of the (AmPyPh)AlMe catalyst having a structure of formula Al1 to Al9, the initiator and the monomer δ-VL is 1:1:(100 to 1000);
[0078] Preferably, in the method for preparing the aliphatic polyester having the structure of formula IV, the conversion rate of the monomer to the polyester is greater than 99%.
[0079] The ligand framework and coordination environment have a great influence on the stability of the catalyst, its tolerance to impurities and subsequent polymerization behavior. We found that by replacing the typical Salen aluminum complex with a structurally similar bispyridine bisphenol ligand, its thermal stability and impurity tolerance were significantly improved, so it showed good tolerance to proton impurities and high activity of low-concentration catalysts in cyclic anhydride / epoxide ring-opening copolymerization. However, the penta-coordinated (BpyBph) aluminum catalyst showed extremely low activity in L-LA ring-opening copolymerization. Although the binary catalytic system composed of (BpyBph)Al alkoxide and alkoxide has high activity, it induces severe epimerization side reactions at high temperatures and provides amorphous PLA. Herein, the present invention designs and synthesizes a tetra-coordinated methylaluminum complex with (aminoalkyl)pyridine-phenol (AmPyPh) chelate. The coordinated AmPyPh is more flexible than the BpyBph ligand and is easily deformed to form an optimal transition state during LA polymerization, thereby increasing the polymerization rate. In addition, since the aluminum center is fully embedded in the AmPyPh tweezers, its heat resistance and impurity tolerance will be further improved. The catalytic performance of these (AmPyPh)Al-Me complexes is much higher than that of most aluminum-based complexes reported so far. (AmPyPh)AlMe can promote the polymerization of L-LA under industrial relevant conditions (150°C, melt) with catalyst concentrations as low as 0.005 mol% to produce colorless semi-crystalline polylactic acid. In addition, using a difunctional alcohol (1,4-butanediol (BDO)) as an initiator, polylactic acid diols (precursors of polyurethanes) with narrow molecular weight distribution and customizable molecular weight can be easily prepared under industrial conditions. Based on this, the present invention synthesized a series of (AmPyPh)Al-Me catalysts with low biotoxicity. These aluminum complexes can efficiently catalyze the polymerization of L-LA, ε-CL and δ-VL under industrial conditions to prepare high molecular weight and low molecular weight distribution PLA, PCL and PVL.
[0080] The present invention adopts an anhydrous and oxygen-free high temperature polymerization method, and uses (AmPyPh)AlMe catalyst to carry out ring-opening polymerization reaction on lactide and / or lactone. Within the polymerization reaction time of the present invention, the monomer conversion rate is ≥98%, and PLA, PCL and PVL with high molecular weight (12.7-128.6KDa) and relatively low molecular weight distribution (1.11-1.67) (industrial use [Sn(Oct)2 ring-opening polymerization obtains PLA with a molecular weight distribution of 1.80-2.00]) can be obtained.
[0081] Compared with the prior art, the present invention has the following advantages and technical effects:
[0082] The present invention provides an (AmPyPh)AlMe catalyst and a preparation method and application thereof. The preparation method of the present invention is simple and efficient, and can directly utilize the AmPyPh ligand to react with an aluminum source. After the reaction is completed, the solvent can be directly drained to obtain the corresponding catalyst. The present invention also utilizes the synthesized catalyst to catalyze monomers such as cyclic esters and lactones to prepare biodegradable aliphatic polyesters, and the monomer conversion rate is greater than 96%. Compared with the currently commercialized stannous isooctanoate catalyst, the (AmPyPh)AlMe catalyst provided by the present invention has higher catalytic activity and lower biological toxicity, and has certain application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0083] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0084] Figure 1 This is a flow chart of the ring-opening polymerization of aliphatic lactones of the present invention;
[0085] Figure 2 is the ligand having the structure of formula LA in Example 1 of the present invention 1 H NMR spectrum;
[0086] Figure 3 is a single crystal diffraction structure diagram of the ligand having the LA structure in Example 1 of the present invention;
[0087] Figure 4 is the ligand having the structure of formula LB in Example 2 of the present invention 1 H NMR spectrum;
[0088] Figure 5 The ligand having the structure of formula LC in Example 3 of the present invention is 1 H NMR spectrum;
[0089] Figure 6 is the ligand having the structure of formula LD in Example 4 of the present invention 1 H NMR spectrum;
[0090] Figure 7 is the ligand having the structure of formula LE in Example 5 of the present invention 1 H NMR spectrum;
[0091] Figure 8 is the ligand having the structure of formula LF in Example 6 of the present invention 1 H NMR spectrum;
[0092] Fig. 9 is the ligand having the structure of formula LG in Example 7 of the present invention 1 H NMR spectrum;
[0093] Fig.10 is the ligand having the structure of formula LH in Example 8 of the present invention 1 H NMR spectrum;
[0094] Fig.11 is the ligand having the structure of formula LI in Example 9 of the present invention 1 H NMR spectrum;
[0095] Fig.12 The (AmPyPh)AlMe catalyst having the structure of formula Al1 in Example 10 of the present invention 1 H NMR spectrum;
[0096] Fig.13 The (AmPyPh)AlMe catalyst having the formula Al2 structure in Example 11 of the present invention 1 H NMR spectrum;
[0097] Fig.14 The (AmPyPh)AlMe catalyst having the structure of formula Al3 in Example 12 of the present invention 1 H NMR spectrum;
[0098] Fig.15 The (AmPyPh)AlMe catalyst having the structure of formula Al4 in Example 13 of the present invention 1 H NMR spectrum;
[0099] Fig.16 1H NMR spectrum of the (AmPyPh)AlMe catalyst having the structure of formula Al5 in Example 14 of the present invention;
[0100] Fig.17 The (AmPyPh)AlMe catalyst having the formula Al6 structure in Example 15 of the present invention 1 H NMR spectrum;
[0101] Fig.18 The (AmPyPh)AlMe catalyst having the structure of formula Al7 in Example 16 of the present invention 1 H NMR spectrum;
[0102] Fig.19 The (AmPyPh)AlMe catalyst having the formula Al8 structure in Example 17 of the present invention 1 H NMR spectrum;
[0103] Fig. 20 The (AmPyPh)AlMe catalyst having the formula Al9 structure in Example 18 of the present invention 1 H NMR spectrum;
[0104] Fig.21 The polyester having the structure of formula II-1 in Example 19 of the present invention 1 H NMR spectrum;
[0105] Fig. 22 The polyester having the structure of formula II-2 in Example 26 of the present invention 1 H NMR spectrum;
[0106] Fig.23 The polyester having the structure of formula III in Example 23 of the present invention 1 H NMR spectrum;
[0107] Fig.24 The polyester having the structure of formula IV in Example 24 of the present invention 1 H NMR spectrum. DETAILED DESCRIPTION
[0108] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0109] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0110] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0111] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0112] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0113] Unless otherwise specified, the room temperature in the present invention is 25±2°C.
[0114] All raw materials used in the examples of the present invention are commercially available.
[0115] In the present invention, during the process of synthesizing the catalyst, the operations involved are performed by professionals familiar with the technical field in an MBraun glove box or using standard Schlenk technology under nitrogen protection unless otherwise specified. At the same time, the solvents involved in the present invention are all anhydrous and oxygen-free solvents.
[0116] In the present invention, in the process of preparing aliphatic polyester by ring-opening polymerization of monomers catalyzed by catalyst, all operations sensitive to moisture and oxygen are carried out by professionals familiar with the technical field in MBraun glove box or using standard Schlenk technology under nitrogen protection.
[0117] In the present invention, the obtained polymer was subjected to relevant tests, the microstructure of the polymer was determined by nuclear magnetic resonance spectroscopy, and the molecular weight and molecular weight distribution index of the polymer were determined by gel chromatography. 1 H and 13 CNMR was measured by Bruker-400 NMR at 25°C, TMS was used as internal standard, deuterated chloroform or deuterated DMSO was used as solvent, and the catalyst was 1 H and 13 C NMR was measured by Bruker-400 and Bruker-800 NMR at 25°C. Gel chromatography was measured by Waters gel permeation chromatograph. Chromatographic grade tetrahydrofuran (THF) was used as solvent (0.05wt% 2,6-di-tert-butyl-4-methylphenol was added as antioxidant), the test temperature was 39.9°C, the flow rate was 1.0mL / min, and PL EasiCalPS-1 was used as standard sample.
[0118] In the present invention, representative embodiments are as follows:
[0119] A preparation method of an (AmPyPh)AlMe catalyst comprises the following steps: mixing an AmPyPh ligand and an aluminum source in a reaction solvent at room temperature, placing the mixture in an oil bath at 100°C for reaction, concentrating the reaction solution after the reaction is completed and performing recrystallization to obtain an (AmPyPh)AlMe catalyst having an Al1-Al9 structure. The method is simple to operate.
[0120]
[0121] Preferably, the aluminum source is trimethylaluminum (AlMe3);
[0122] Preferably, the reaction solvent is toluene.
[0123] The technical solution of the present invention is further illustrated by the following embodiments.
[0124] Figure 1 This is a flow chart of the ring-opening polymerization of aliphatic lactones of the present invention. It can be seen that the (AmPyPh)AlMe catalyst of the present invention can efficiently catalyze the ring-opening polymerization of a series of aliphatic lactones to generate corresponding polyesters.
[0125] Examples 1 to 9 are the preparation processes of AmPyPh ligands.
[0126] Example 1
[0127] Synthesis of the ligand having the structure shown in Formula LA: Select 2-(tert-butyl)-4-fluoro-6-(4,4,5,5-tetramethyl-1,3-dioxaboryl)phenol with F-substitution group, weigh 1.3 equivalents of 6-bromopyridine-2-carboxaldehyde, add them to the side-mouth flask, add methanol and saturated sodium carbonate solution; connect the reflux device and evacuate the dissolved oxygen in the suspension, add tetrakis(triphenylphosphine palladium) (Pd(PPh3)4) toluene solution under nitrogen protection for coupling reaction, the reaction temperature is 130°C, and the reaction time is 20h. After the reaction is completed, use ethyl acetate to extract, stand and separate, take the upper oil phase, dry it with anhydrous magnesium sulfate, and then rotary evaporate to obtain a crude product, which is purified by column chromatography, and eluted with PE / EA (petroleum ether / ethyl acetate) phase, the elution ratio is PE / EA=85 / 15 (volume ratio, the same below), and the first step product is obtained. After obtaining the first step product, it is fully dissolved in methanol, 1.5 equivalents of 2,6-diisopropylaniline is added, and Mannich reaction is carried out under the catalysis of p-toluenesulfonic acid, the reaction temperature is 40°C; the reaction time is 24h, and after the reaction is completed, suction filtration is performed, and methanol is rinsed and purified to obtain the second step product. The fully dried second step product is added to the branched flask, a double-row tube is connected, anhydrous oxygen-free ether is added to the branched flask, the branched flask is placed in a low temperature environment of -78°C, 2.0 equivalents of phenyl lithium solution (2.0 mol / L) are added, stirred at low temperature (-78°C, the same below) for 1h, and reacted at room temperature for 15h; after the reaction is completed, a saturated ammonium chloride aqueous solution is added for quenching, and ethyl acetate is used for extraction, and the liquid is separated after standing, and the upper oil phase is taken, dried over anhydrous magnesium sulfate, and then rotary evaporated to obtain a crude product, which is purified by column chromatography and eluted with PE / EA phase, and the eluent ratio is PE / EA=95 / 5 (volume ratio, the same below). After the solvent was dried, methanol was used for recrystallization to obtain a pale white oily solid, which was the ligand having the structure shown in Formula LA, with a yield of 50%. 1H spectrum and single crystal diffraction characterization, such as Figure 1 and Figure 2 As shown, the obtained ligand was determined to have the structure shown in Formula LA by NMR and single crystal diffraction characterization.
[0128] Example 2
[0129] Synthesis of a ligand having a structure shown in Formula LB: Select 2-(tert-butyl)-4-tert-butyl-6-(4,4,5,5-tetramethyl-1,3-dioxaboryl)phenol with t-Bu substituent, weigh 1.3 equivalents of 6-bromopyridine-2-carboxaldehyde, add them to a branched flask, add methanol and saturated sodium carbonate solution; connect a reflux device and evacuate the dissolved oxygen in the suspension, then add a toluene solution of Pd(PPh3)4 under nitrogen protection for coupling reaction, the reaction temperature is 130°C, and the reaction time is 20h. After the reaction is completed, extract with ethyl acetate, let stand and separate, take the upper oil phase, dry with anhydrous magnesium sulfate and then rotary evaporate to obtain a crude product, purify by column chromatography, use PE / EA phase for elution, the elution ratio is PE / EA=85 / 15, and obtain the first step product. After obtaining the first step product, fully dissolve it in methanol, add 1.5 equivalents of 2,6-diisopropylaniline, and perform Mannich reaction under the catalysis of p-toluenesulfonic acid. The reaction temperature is 40°C and the reaction time is 24h. After the reaction is completed, filter it with suction, rinse it with methanol and purify it to obtain the second step product. Add the fully dried second step product to the branched flask. Connect a double-row tube, add anhydrous oxygen-free ether to the branched flask, place the branched flask in a low temperature environment of -78°C, add 2.0 equivalents of phenyl lithium solution (2.0 mol / L), stir at low temperature for 1h, and then react at room temperature for 15h; after the reaction is completed, add saturated ammonium chloride aqueous solution for quenching, extract with ethyl acetate, stand and separate, take the upper oil phase, dry it with anhydrous magnesium sulfate, and then rotary evaporate to obtain a crude product, purify it by column chromatography, and elute it with PE / EA phase, and the eluent ratio is PE / EA=100 / 0. After the solvent was dried, methanol was used for recrystallization to obtain a white oily solid, which was the ligand having the structure shown in formula LB, with a yield of 60%. 1 H spectrum characterization, such as Figure 3 As shown, the obtained ligand was determined to have the structure shown in Formula LB by NMR characterization.
[0130] Example 3
[0131] Synthesis of the ligand having the structure shown in Formula LC: Select 2-(tert-butyl)-4-methoxy-6-(4,4,5,5-tetramethyl-1,3-dioxaboryl)phenol with OCH3 as the substituent, and weigh 1.3 equivalents of 6-bromopyridine-2-carboxaldehyde, add them to the branched flask, add methanol and saturated sodium carbonate solution; connect the reflux device and evacuate the dissolved oxygen in the suspension, and then add Pd(PPh3)4 toluene solution under nitrogen protection for coupling reaction, the reaction temperature is 130°C, and the reaction time is 20h. After the reaction is completed, use ethyl acetate to extract, stand and separate, take the upper oil phase, dry it with anhydrous magnesium sulfate, and then rotary evaporate to obtain a crude product, which is purified by column chromatography, and eluted with PE / EA phase, with an elution ratio of PE / EA=85 / 15 to obtain the first step product. After obtaining the first step product, fully dissolve it in methanol, add 1.5 equivalents of 2,6-diisopropylaniline, and perform Mannich reaction under the catalysis of p-toluenesulfonic acid. The reaction temperature is 40°C and the reaction time is 24h. After the reaction is completed, filter and purify with methanol to obtain the second step product. Add the fully dried second step product to the branched flask. Connect a double-row tube, add anhydrous oxygen-free ether to the branched flask, place the branched flask in a low temperature environment of -78°C, add 2.0 equivalents of phenyl lithium solution (2.0 mol / L), stir at low temperature for 1h, and react at room temperature for 15h; after the reaction is completed, add saturated ammonium chloride aqueous solution for quenching, extract with ethyl acetate, stand and separate, take the upper oil phase, dry with anhydrous magnesium sulfate and rotary evaporate to obtain a crude product, purify by column chromatography, and elute with PE / EA phase, and the eluent ratio is PE / EA=95 / 5. After the solvent was dried, methanol was used for recrystallization to obtain a yellow oily solid, which was the ligand having the structure shown in the formula LC, with a yield of 90%. 1 H spectrum characterization, such as Figure 4 As shown, the obtained ligand was determined to have the structure shown in formula LC by NMR characterization.
[0132] Example 4
[0133] Synthesis of the ligand having the structure shown in Formula LD: Select 2-(tert-butyl)-4-fluoro-6-(4,4,5,5-tetramethyl-1,3-dioxaboryl)phenol with F-substitution group, weigh 1.3 equivalents of 6-bromopyridine-2-carboxaldehyde, add them to the side-mouth flask, add methanol and saturated sodium carbonate solution; connect the reflux device and evacuate the dissolved oxygen in the suspension, then add Pd(PPh3)4 toluene solution under nitrogen protection for coupling reaction, the reaction temperature is 130°C, and the reaction time is 20h. After the reaction is completed, use ethyl acetate to extract, let it stand and separate the liquids, take the upper oil phase, dry it with anhydrous magnesium sulfate, and then rotary evaporate to obtain a crude product, which is purified by column chromatography, and eluted with PE / EA phase, with an elution ratio of PE / EA=85 / 15 to obtain the first step product. After obtaining the first step product, fully dissolve it in methanol, add 1.5 equivalents of 2,6-diisopropylaniline, and perform Mannich reaction under the catalysis of p-toluenesulfonic acid. The reaction temperature is 40°C and the reaction time is 24h. After the reaction is completed, filter and purify with methanol to obtain the second step product. Add the fully dried second step product to the branched flask. Connect a double-row tube, add anhydrous oxygen-free ether to the branched flask, place the branched flask in a low temperature environment of -78°C, add 2.3 equivalents of methyl lithium solution (1.0 mol / L), stir at low temperature for 1h, and then react at room temperature for 15h; after the reaction is completed, add saturated ammonium chloride aqueous solution for quenching, extract with ethyl acetate, stand and separate, take the upper oil phase, dry with anhydrous magnesium sulfate and rotary evaporate to obtain a crude product, purify by column chromatography, and elute with PE / EA phase, and the eluent ratio is PE / EA=95 / 5. After the solvent was dried, methanol was used for recrystallization to obtain a light yellow oily solid, which was the ligand having the structure shown in formula LD, with a yield of 60%. 1 H spectrum characterization, such as Figure 5 As shown, the obtained ligand was determined to have the structure shown in formula LD by NMR characterization.
[0134] Example 5
[0135] Synthesis of a ligand having a structure shown in formula LE: Select 2-(tert-butyl)-4-fluoro-6-(4,4,5,5-tetramethyl-1,3-dioxaboryl)phenol with a F-substituted group, weigh 1.3 equivalents of 6-bromopyridine-2-carboxaldehyde, add them to a branched flask, add methanol and saturated sodium carbonate solution; connect a reflux device and evacuate the dissolved oxygen in the suspension, then add a toluene solution of Pd(PPh3)4 under nitrogen protection for coupling reaction, the reaction temperature is 130°C, and the reaction time is 20h. After the reaction is completed, extract with ethyl acetate, let stand and separate, take the upper oil phase, dry with anhydrous magnesium sulfate, and then rotary evaporate to obtain a crude product, which is purified by column chromatography, eluted with PE / EA phase, and the elution ratio is PE / EA=85 / 15 to obtain the first step product. After obtaining the first step product, fully dissolve it in methanol, add 1.5 equivalents of 2,6-diisopropylaniline, and perform Mannich reaction under the catalysis of p-toluenesulfonic acid. The reaction temperature is 40°C and the reaction time is 24h. After the reaction is completed, filter it with suction, rinse it with methanol and purify it to obtain the second step product. Add the fully dried second step product to the branched flask. Connect a double-row tube, add anhydrous oxygen-free ether to the branched flask, place the branched flask in a low temperature environment of -78°C, add 2.3 equivalents of isopropyl lithium solution (1.0 mol / L), stir at low temperature for 1h, and then react at room temperature for 15h; after the reaction is completed, add saturated ammonium chloride aqueous solution for quenching, extract with ethyl acetate, stand and separate, take the upper oil phase, dry it with anhydrous magnesium sulfate, and then rotary evaporate to obtain a crude product, purify it by column chromatography, and elute it with PE / EA phase, and the eluent ratio is PE / EA=75 / 25. After the solvent was dried, methanol was used for recrystallization to obtain a pale white oily solid, which was the ligand having the structure shown in Formula LE, with a yield of 50%. 1 H spectrum characterization, such as Figure 6 As shown, the obtained ligand was determined to have the structure shown in formula LE by NMR characterization.
[0136] Example 6
[0137] Synthesis of the ligand having the structure shown in formula LF: Select 2-(tert-butyl)-4-fluoro-6-(4,4,5,5-tetramethyl-1,3-dioxaboryl)phenol with F-substitution group, weigh 1.3 equivalents of 6-bromopyridine-2-carboxaldehyde, add them to the side-mouth flask, add methanol and saturated sodium carbonate solution; connect the reflux device and evacuate the dissolved oxygen in the suspension, then add Pd(PPh3)4 toluene solution under nitrogen protection for coupling reaction, the reaction temperature is 130°C, and the reaction time is 20h. After the reaction is completed, use ethyl acetate to extract, stand and separate, take the upper oil phase, dry it with anhydrous magnesium sulfate and then rotary evaporate to obtain a crude product, purify it by column chromatography, use PE / EA phase for elution, and the elution ratio is PE / EA=85 / 15 to obtain the first step product. After obtaining the first step product, fully dissolve it in methanol, add 1.5 equivalents of 2,6-diisopropylaniline, and perform Mannich reaction under the catalysis of p-toluenesulfonic acid. The reaction temperature is 40°C and the reaction time is 24h. After the reaction is completed, filter and purify with methanol to obtain the second step product. Add the fully dried second step product to the branched flask. Connect a double-row tube, add anhydrous oxygen-free ether to the branched flask, place the branched flask in a low temperature environment of -78°C, add 2.3 equivalents of lithium aluminum hydride solution (1.0 mol / L), stir at low temperature for 1h, and react at room temperature for 15h; after the reaction is completed, add saturated ammonium chloride aqueous solution for quenching, extract with ethyl acetate, stand and separate, take the upper oil phase, dry with anhydrous magnesium sulfate and rotary evaporate to obtain a crude product, purify by column chromatography, and elute with PE / EA phase, and the eluent ratio is PE / EA=75 / 25. After the solvent was dried, methanol was used for recrystallization to obtain a yellow solid, which was the ligand having the structure shown in Formula LF, with a yield of 50%. 1 H spectrum characterization, such as Figure 7 As shown, the obtained ligand was determined to have the structure shown in Formula LF by NMR characterization.
[0138] Example 7
[0139] Synthesis of the ligand having the structure shown in formula LG: Select 2-(tert-butyl)-4-fluoro-6-(4,4,5,5-tetramethyl-1,3-dioxaboryl)phenol with F-substitution group, weigh 1.3 equivalents of 6-bromopyridine-2-carboxaldehyde, add them to the side-mouth flask, add methanol and saturated sodium carbonate solution; connect the reflux device and evacuate the dissolved oxygen in the suspension, then add Pd(PPh3)4 toluene solution under nitrogen protection for coupling reaction, the reaction temperature is 130°C, and the reaction time is 20h. After the reaction is completed, use ethyl acetate to extract, stand and separate, take the upper oil phase, dry it with anhydrous magnesium sulfate and then rotary evaporate to obtain a crude product, perform column chromatography purification, use PE / EA phase for elution, and the elution ratio is PE / EA=85 / 15 to obtain the first step product. After obtaining the first step product, fully dissolve it in methanol, add 1.5 equivalents of 4-fluoroaniline, and carry out Mannich reaction under the catalysis of p-toluenesulfonic acid. The reaction temperature is 40°C and the reaction time is 24h. After the reaction, filter and purify with methanol. Add the fully dried second step product to the branched flask. Connect a double-row tube, add anhydrous oxygen-free ether to the branched flask, place the branched flask in a low temperature environment of -78°C, add 2.3 equivalents of phenyl lithium solution (1.9mol / L), stir at low temperature for 1h, and then react at room temperature for 15h; after the reaction, add saturated ammonium chloride aqueous solution for quenching, extract with ethyl acetate, stand and separate, take the upper oil phase, dry with anhydrous magnesium sulfate and then rotary evaporate to obtain a crude product, purify by column chromatography, and elute with PE / EA phase, the eluent ratio is PE / EA=95 / 5. After the solvent is dried, use methanol for recrystallization to obtain a light yellow solid, which is a ligand with the structure shown in formula LG, with a yield of 40%. The obtained ligand was subjected to NMR 1 H spectrum characterization, such as Figure 8 As shown, the obtained ligand was determined to have the structure shown in formula LG by NMR characterization.
[0140] Example 8
[0141] Synthesis of the ligand having the structure shown in formula LH: Select 2-(tert-butyl)-4-fluoro-6-(4,4,5,5-tetramethyl-1,3-dioxaboryl)phenol with F-substitution group, weigh 1.3 equivalents of 6-bromopyridine-2-carboxaldehyde, add them to the branched flask, add methanol and saturated sodium carbonate solution; connect the reflux device and evacuate the dissolved oxygen in the suspension, then add Pd(PPh3)4 toluene solution under nitrogen protection for coupling reaction, the reaction temperature is 130°C, and the reaction time is 20h. After the reaction is completed, use ethyl acetate to extract, stand and separate, take the upper oil phase, dry it with anhydrous magnesium sulfate and then rotary evaporate to obtain a crude product, purify it by column chromatography, use PE / EA phase for elution, and the elution ratio is PE / EA=85 / 15 to obtain the first step product. After obtaining the first step product, fully dissolve it in methanol, add 1.5 equivalents of aniline, and carry out Mannich reaction under the catalysis of p-toluenesulfonic acid. The reaction temperature is 40°C and the reaction time is 24h. After the reaction, filter and purify with methanol. Add the fully dried second step product to the branched flask. Connect a double-row tube, add anhydrous and oxygen-free ether to the branched flask, place the branched flask in a low temperature environment of -78°C, add 2.3 equivalents of phenyl lithium solution (1.9mol / L), stir at low temperature for 1h, and then react at room temperature for 15h; after the reaction, add saturated ammonium chloride aqueous solution for quenching, extract with ethyl acetate, stand and separate, take the upper oil phase, dry with anhydrous magnesium sulfate, and then rotary evaporate to obtain a crude product, purify with column chromatography, and elute with PE / EA phase, and the eluent ratio is PE / EA=95 / 5. After the solvent is dried, use methanol for recrystallization to obtain a light green solid, which is the ligand with the structure shown in formula LH, with a yield of 30%. The obtained ligand is subjected to nuclear magnetic resonance. 1 H spectrum characterization, such as Fig. 9 As shown, the obtained ligand was determined to have the structure shown in formula LH by NMR characterization.
[0142] Example 9
[0143] Synthesis of the ligand having the structure shown in Formula LI: Select 2-(tert-butyl)-4-fluoro-6-(4,4,5,5-tetramethyl-1,3-dioxaboryl)phenol with F-substitution group, weigh 1.3 equivalents of 6-bromopyridine-2-carboxaldehyde, add them to the branched flask, add methanol and saturated sodium carbonate solution; connect the reflux device and evacuate the dissolved oxygen in the suspension, then add Pd(PPh3)4 toluene solution under nitrogen protection for coupling reaction, the reaction temperature is 130°C, and the reaction time is 20h. After the reaction is completed, use ethyl acetate to extract, stand and separate, take the upper oil phase, dry it with anhydrous magnesium sulfate and then rotary evaporate to obtain a crude product, purify it by column chromatography, use PE / EA phase for elution, and the elution ratio is PE / EA=85 / 15 to obtain the first step product. After obtaining the first step product, it is fully dissolved in methanol, 1.5 equivalents of 4-methoxyaniline are added, and Mannich reaction is carried out under the catalysis of p-toluenesulfonic acid. The reaction temperature is 40°C and the reaction time is 24h. After the reaction is completed, suction filtration is performed, and methanol is rinsed and purified to obtain the second step product. The fully dried second step product is added to the branched flask. Connect a double-row tube, add anhydrous oxygen-free ether to the branched flask, place the branched flask in a low temperature environment of -78°C, add 2.3 equivalents of phenyl lithium solution (1.9mol / L), stir at low temperature for 1h, and then react at room temperature for 15h; after the reaction is completed, add saturated ammonium chloride aqueous solution for quenching, use ethyl acetate to extract, stand and separate, take the upper oil phase, dry with anhydrous magnesium sulfate, and then rotary evaporate to obtain a crude product, use column chromatography to purify, and use PE / EA phase for elution, and the eluent ratio is PE / EA=95 / 5. After the solvent is dried, use methanol for recrystallization to obtain a yellow solid, which is a ligand with a structure shown in formula LI, with a yield of 50%. The obtained ligand was subjected to NMR 1 H spectrum characterization, such as Fig.10 As shown, the obtained ligand was determined to have the structure shown in Formula LI by NMR characterization.
[0144] Examples 10 to 18 are the preparation processes of (AmPyPh)AlMe catalysts having structures of formula Al1 to Al9.
[0145] Example 10
[0146] Synthesis of (AmPyPh)AlMe catalyst with Al1 structure: Under nitrogen atmosphere, dissolve the ligand with LA structure (0.51 g, 1 mmol) in a pressure bottle containing 5.0 mL of dry toluene, slowly drop 1.0 mL of trimethylaluminum n-hexane solution (2.0 mol / L) into the pressure bottle, seal it and heat it to 100°C for reaction. The reaction time is 24 hours. After the reaction, drain the solvent and use ultra-dry n-hexane for recrystallization. After purification, obtain the aluminum complex, which is the (AmPyPh)AlMe catalyst. The obtained aluminum complex was subjected to nuclear magnetic resonance.1 H spectrum characterization, such as Fig.11 As shown, it can be determined through NMR characterization that the obtained aluminum complex has the structure shown in formula Al1.
[0147] Embodiment 11
[0148] Synthesis of (AmPyPh)AlMe catalyst with Al2 structure: Under nitrogen atmosphere, ligand with LB structure (0.53 g, 1 mmol) was dissolved in a pressure bottle containing 5.0 mL dry toluene, 1.0 mL trimethylaluminum n-hexane solution (2.0 mol / L) was slowly added to the pressure bottle, sealed and heated to 100°C for reaction, the reaction time was 24 h, the solvent was drained after the reaction, and ultra-dry n-hexane was used for recrystallization, and the aluminum complex was obtained after purification, namely (AmPyPh)AlMe catalyst. The obtained aluminum complex was subjected to nuclear magnetic resonance. 1 H spectrum characterization, such as Fig.12 As shown, nuclear magnetic resonance characterization can also determine that the obtained aluminum complex has the structure shown in formula Al2.
[0149] Example 12
[0150] Synthesis of (AmPyPh)AlMe catalyst with Al3 structure: Under nitrogen atmosphere, ligand with LC structure (0.55 g, 1 mmol) was dissolved in a pressure bottle containing 5.0 mL dry toluene, 1.0 mL trimethylaluminum n-hexane solution (2.0 mol / L) was slowly added to the pressure bottle, sealed and heated to 100°C for reaction, the reaction time was 24 h, after the reaction was completed, the solvent was drained, and ultra-dry n-hexane was used for recrystallization, and the aluminum complex was obtained after purification, namely (AmPyPh)AlMe catalyst. The obtained aluminum complex was subjected to nuclear magnetic resonance. 1 H spectrum characterization, such as Fig.13 As shown, the obtained aluminum complex was determined to have the structure shown in formula Al3 by NMR characterization.
[0151] Example 13
[0152] Synthesis of (AmPyPh)AlMe catalyst with Al4 structure: Under nitrogen atmosphere, dissolve the ligand with LD structure (0.45 g, 1 mmol) in a pressure bottle containing 5.0 mL of dry toluene, slowly drop 1.0 mL of trimethylaluminum n-hexane solution (2.0 mol / L) into the pressure bottle, seal it and heat it to 100°C for reaction. The reaction time is 24 hours. After the reaction is completed, drain the solvent and use ultra-dry n-hexane for recrystallization. After purification, obtain the aluminum complex, which is the (AmPyPh)AlMe catalyst. The obtained aluminum complex was subjected to nuclear magnetic resonance. 1 H spectrum characterization, such as Fig.14As shown, nuclear magnetic resonance characterization can also determine that the obtained aluminum complex has the structure shown in formula Al4.
[0153] Embodiment 14
[0154] Synthesis of (AmPyPh)AlMe catalyst with Al5 structure: Under nitrogen atmosphere, dissolve the ligand with LE structure (0.48 g, 1 mmol) in a pressure bottle containing 5.0 mL of dry toluene, slowly drop 1.0 mL of trimethylaluminum n-hexane solution (2.0 mol / L) into the pressure bottle, seal it and heat it to 100 °C for reaction. The reaction time is 24 hours. After the reaction is completed, drain the solvent and use ultra-dry n-hexane for recrystallization. After purification, obtain the aluminum complex, which is the (AmPyPh)AlMe catalyst. The obtained aluminum complex was subjected to nuclear magnetic resonance. 1 H spectrum characterization, such as Fig.15 As shown, nuclear magnetic resonance characterization can also determine that the obtained aluminum complex has the structure shown in formula Al5.
[0155] Embodiment 15
[0156] Synthesis of AmPyPh-catalyst with Al6 structure: Under nitrogen atmosphere, the ligand with LF structure (0.43 g, 1 mmol) was dissolved in a pressure bottle containing 5.0 mL of dry toluene, and 1.0 mL of trimethylaluminum n-hexane solution (2.0 mol / L) was slowly added to the pressure bottle. After sealing, it was heated to 100 ° C for reaction. The reaction time was 24 hours. After the reaction, the solvent was drained and recrystallized using ultra-dry n-hexane. After purification, the aluminum complex was obtained, which was the (AmPyPh)AlMe catalyst. The obtained aluminum complex was subjected to nuclear magnetic resonance. 1 H spectrum characterization, such as Fig.16 As shown, nuclear magnetic resonance characterization can also determine that the obtained aluminum complex has the structure shown in formula Al6.
[0157] Example 16
[0158] Synthesis of (AmPyPh)AlMe catalyst with Al7 structure: Under nitrogen atmosphere, a ligand with LG structure (0.44 g, 1 mmol) was dissolved in a pressure bottle containing 5.0 mL of dry toluene. 1.0 mL of methylaluminum n-hexane solution (2.0 mol / L) was slowly added dropwise into the pressure bottle. The bottle was sealed and heated to 100°C for reaction. The reaction time was 24 h. After the reaction, the solvent was drained and recrystallized using ultra-dry n-hexane. After purification, an aluminum complex was obtained, which was the (AmPyPh)AlMe catalyst.
[0159] Embodiment 17
[0160] Synthesis of (AmPyPh)AlMe catalyst with Al8 structure: Under nitrogen atmosphere, a ligand with LH structure (0.43 g, 1 mmol) was dissolved in a pressure bottle containing 5.0 mL of dry toluene. 1.0 mL of trimethylaluminum n-hexane solution (2.0 mol / L) was slowly added dropwise into the pressure bottle. The bottle was sealed and heated to 100°C for reaction. The reaction time was 24 h. After the reaction, the solvent was drained and recrystallized using ultra-dry n-hexane. After purification, an aluminum complex was obtained, namely the (AmPyPh)AlMe catalyst.
[0161] Embodiment 18
[0162] Synthesis of (AmPyPh)AlMe catalyst with Al9 structure: Under nitrogen atmosphere, a ligand with LI structure (0.46 g, 1 mmol) was dissolved in a pressure bottle containing 5.0 mL of dry toluene. 1.0 mL of trimethylaluminum n-hexane solution (2.0 mol / L) was slowly added dropwise into the pressure bottle. The bottle was sealed and heated to 100°C for reaction. The reaction time was 24 h. After the reaction, the solvent was drained and recrystallized using ultra-dry n-hexane. After purification, an aluminum complex was obtained, namely the (AmPyPh)AlMe catalyst.
[0163] The (AmPyPh)AlMe catalyst having the structure of formula Al1 to Al9 can successfully catalyze the ring-opening homopolymerization of lactide (L-LA or rac-LA), ε-caprolactone (ε-CL) and δ-valerolactone (δ-VL) to generate polylactic acid (PLA), polycaprolactone (PCL) and polyvalerolactone (PVL) under the condition that benzyl alcohol is preferably used as an initiator. Representative embodiments are shown in Examples 19 to 53.
[0164] Embodiment 19
[0165] The catalyst used for PLLA of this embodiment is (AmPyPh)AlMe catalyst having a structure of formula Al9 (hereinafter referred to as "catalyst Al9").
[0166] The preparation method of PLLA in this embodiment comprises the following steps:
[0167] (1) In an inert atmosphere, 1 μmol of benzyl alcohol was added to a dry 15 mL pressure bottle, followed by 1 μmol of catalyst Al9 and finally 1000 μmol of L-LA. The bottle was sealed and placed in a stable environment at 150°C for polymerization reaction for 1.5 h under stirring.
[0168] (2) After the polymerization is completed, the pressure bottle is cooled to room temperature, and dichloromethane is added to dissolve the obtained polymer to obtain a polymer solution. The polymer solution is then uniformly poured into ethanol (reverse precipitation), filtered, and vacuum dried to obtain PLLA.
[0169] The polymerization time was 1.5 h, and the conversion rate of L-LA monomer reached 96%. The catalytic activity of catalyst Al9 was higher than that of the catalyst reported in the literature (Eur. Polym. J. 122, 5, 109302). The above-obtained product (i.e., PLLA) was subjected to GPC analysis and NMR analysis. Fig.21 As shown, the product obtained in Example 19 of the present invention is a polyester having a structure of formula II-1, with an actual molecular weight of 58.3 KDa and a molecular weight distribution of 1.30.
[0170] Embodiment 20
[0171] The catalyst used in the PLA-BDO-PLA of this embodiment is catalyst Al9.
[0172] The preparation method of PLLA in this embodiment comprises the following steps:
[0173] (1) In an inert atmosphere, add 1 μmol of BDO (1,4-butanediol) into a dry 15 mL pressure bottle, then add 1 μmol of catalyst Al9, and finally add 1000 μmol of L-LA. After sealing, place in a stable environment at 150°C and perform polymerization reaction for 2 h under stirring.
[0174] (2) After the polymerization is completed, the pressure bottle is cooled to room temperature, and dichloromethane is added to dissolve the obtained polymer to obtain a polymer solution. The polymer solution is then uniformly poured into ethanol, filtered, and vacuum dried to obtain PLA-BDO-PLA.
[0175] The polymerization time was 2 hours, and the conversion rate of L-LA monomer reached 96.0%. The above-obtained product (ie, PLA-BDO-PLA) was analyzed by GPC, and its actual molecular weight was 110.0 KDa, and the molecular weight distribution was 1.33.
[0176] Embodiment 21
[0177] The catalyst used for PLLA in this embodiment is catalyst Al9.
[0178] The preparation method of PLLA in this embodiment comprises the following steps:
[0179] (1) In an inert atmosphere, 1 μmol of benzyl alcohol was added to a dry 15 mL pressure bottle, followed by 1 μmol of catalyst Al9 (i.e., 0.005 mol% of the catalyst relative to the monomer), and finally 20,000 μmol of L-LA was added. The bottle was sealed and placed in a stable environment at 150° C., and the polymerization reaction was carried out for 168 hours under stirring;
[0180] (2) After the polymerization is completed, the pressure bottle is cooled to room temperature, and dichloromethane is added to dissolve the obtained polymer to obtain a polymer solution. The polymer solution is then uniformly poured into ethanol (reverse precipitation), filtered, and vacuum dried to obtain PLLA.
[0181] The polymerization time was 168h, and the conversion rate of L-LA monomer reached 92.0%. Catalyst Al9 had extremely high thermal stability and would not be deactivated even at high temperature for a long time. The above-obtained product (i.e., PLLA) was subjected to GPC analysis and NMR analysis. Fig.21 As shown, the product obtained in Example 21 of the present invention is a polyester having a structure of formula II-1, with an actual molecular weight of 58.3 KDa and a molecular weight distribution of 1.45.
[0182] Embodiment 22
[0183] The catalyst used for PLLA in this embodiment is catalyst Al9.
[0184] The preparation method of PLLA in this embodiment comprises the following steps:
[0185] (1) In an inert atmosphere, 1 μmol of benzyl alcohol was added to a dry 15 mL pressure bottle, followed by 1 μmol of catalyst Al9, and finally 20,000 μmol of L-LA (the L-LA monomer used was industrial grade, not purified, and only vacuum dried), and the bottle was sealed and placed in a stable environment at 180° C., and the polymerization reaction was carried out for 110 hours under stirring;
[0186] (2) After the polymerization is completed, the pressure bottle is cooled to room temperature, and dichloromethane is added to dissolve the obtained polymer to obtain a polymer solution. The polymer solution is then uniformly poured into ethanol (reverse precipitation), filtered, and vacuum dried to obtain PLLA.
[0187] The polymerization time was 110 hours, and the conversion rate of L-LA monomer reached 94.2%. Catalyst Al9 has extremely high thermal stability and will not be deactivated even after long-term reaction at high temperature. Even in the presence of industrial-grade monomers with impurities, Al9 has good catalytic activity. The above-obtained product (i.e., PLLA) was subjected to GPC analysis and NMR analysis. The product obtained in Example 22 of the present invention is a polyester having a structure of formula II-1, with an actual molecular weight of 35.6 KDa and a molecular weight distribution of 1.45.
[0188] Embodiment 23
[0189] The catalyst used for PCL in this embodiment is catalyst Al9.
[0190] The preparation method of PCL in this embodiment comprises the following steps:
[0191] (1) In an inert atmosphere, 1 μmol of benzyl alcohol was added to a dry 15 mL pressure bottle, followed by 1 μmol of catalyst Al9 and finally 1000 μmol of ε-CL. The bottle was sealed and placed in a stable environment at 150°C for polymerization reaction for 0.5 h under stirring.
[0192] (2) After the polymerization is completed, the pressure bottle is cooled to room temperature, and dichloromethane is added to dissolve the obtained polymer to obtain a polymer solution. The polymer solution is then uniformly poured into ethanol, filtered, and vacuum dried to obtain PCL.
[0193] The polymerization time was 0.5 h, and the conversion rate of ε-CL monomer reached 100%. The above-obtained product (i.e., PCL) was subjected to GPC analysis and NMR analysis. Fig.23 As shown, the product obtained in Example 23 of the present invention is a polyester having a structure of Formula III, with an actual molecular weight of 135.0 KDa and a molecular weight distribution of 1.32.
[0194] Embodiment 24
[0195] The catalyst used in the PVL of this embodiment is catalyst Al9.
[0196] The preparation method of PVL in this embodiment comprises the following steps:
[0197] (1) In an inert atmosphere, 1 μmol of benzyl alcohol was added to a dry 15 mL pressure bottle, followed by 1 μmol of catalyst Al9 and finally 1000 μmol of δ-VL. The bottle was sealed and placed in a stable environment at 100 °C for polymerization reaction for 1 h under stirring.
[0198] (2) After the polymerization is completed, the pressure bottle is cooled to room temperature, dichloromethane is added to dissolve the obtained polymer to obtain a polymer solution, and then the polymer solution is uniformly poured into ethanol, filtered and vacuum dried to obtain PVL.
[0199] The polymerization time was 0.5 h, and the conversion rate of δ-VL monomer reached 99%. The product (PVL) obtained above was subjected to GPC analysis and NMR analysis. Fig.24 As shown, the product obtained in Example 24 of the present invention is a polyester having a structure of Formula IV, with an actual molecular weight of 118.0 KDa and a molecular weight distribution of 1.35.
[0200] Embodiment 25
[0201] The catalyst used for PLLA in this embodiment is catalyst Al1.
[0202] The preparation method of PLLA in this embodiment comprises the following steps:
[0203] (1) In an inert atmosphere, 1 μmol of benzyl alcohol was added to a dry 15 mL pressure bottle, followed by 1 μmol of catalyst Al1, and finally 1000 μmol of L-LA. The bottle was sealed and placed in a stable environment at 150°C for polymerization reaction for 16 h under stirring.
[0204] (2) After the polymerization is completed, the pressure bottle is cooled to room temperature, and dichloromethane is added to dissolve the obtained polymer to obtain a polymer solution. The polymer solution is then uniformly poured into ethanol (reverse precipitation), filtered, and vacuum dried to obtain PLLA.
[0205] The polymerization time was 16 hours, and the conversion rate of L-LA monomer reached 97.1%. The above-obtained product (i.e., PLLA) was subjected to GPC analysis and NMR analysis. The product obtained in Example 25 of the present invention was a polyester having a structure of Formula II-1, with an actual molecular weight of 73.0 KDa and a molecular weight distribution of 1.67.
[0206] Embodiment 26
[0207] The catalyst used for PLA in this embodiment is catalyst Al1.
[0208] The preparation method of PLA in this embodiment comprises the following steps:
[0209] (1) In an inert atmosphere, 1 μmol of benzyl alcohol was added to a dry 15 mL pressure bottle, followed by 1 μmol of catalyst Al1, and finally 1000 μmol of rac-LA (racemic lactide). The bottle was sealed and placed in a stable environment at 150°C for polymerization reaction for 6 h under stirring.
[0210] (2) After the polymerization is completed, the pressure bottle is cooled to room temperature, dichloromethane is added to dissolve the obtained polymer to obtain a polymer solution, and then the polymer solution is uniformly poured into ethanol, filtered and vacuum dried to obtain PLA.
[0211] The polymerization time was 16 h, and the conversion rate of rac-LA monomer reached 98%. The above-obtained product (i.e., PLA) was subjected to GPC analysis and NMR analysis. Fig. 22 As shown, the product obtained in Example 26 of the present invention is a polyester having a structure of formula II-2, with an actual molecular weight of 89.7 KDa and a molecular weight distribution of 1.59.
[0212] Embodiment 27
[0213] The catalyst used for PCL in this embodiment is catalyst Al1.
[0214] The preparation method of PCL in this embodiment comprises the following steps:
[0215] (1) In an inert atmosphere, 1 μmol of benzyl alcohol was added to a dry 15 mL pressure bottle, followed by 1 μmol of catalyst Al1, and finally 1000 μmol of ε-CL. The bottle was sealed and placed in a stable environment at 150°C for polymerization reaction for 0.5 h under stirring.
[0216] (2) After the polymerization is completed, the pressure bottle is cooled to room temperature, and dichloromethane is added to dissolve the obtained polymer to obtain a polymer solution. The polymer solution is then uniformly poured into ethanol, filtered, and vacuum dried to obtain PCL.
[0217] The polymerization time was 0.5 h, and the conversion rate of ε-CL monomer reached 100%. The above-obtained product (ie PCL) was subjected to GPC analysis and NMR analysis. The product obtained in Example 27 of the present invention was a polyester having a structure of Formula III, with an actual molecular weight of 128.6 KDa and a molecular weight distribution of 1.57.
[0218] Embodiment 28
[0219] The catalyst used in the PVL of this embodiment is catalyst Al1.
[0220] The preparation method of PVL in this embodiment comprises the following steps:
[0221] (1) In an inert atmosphere, 1 μmol of benzyl alcohol was added to a dry 15 mL pressure bottle, followed by 1 μmol of catalyst Al1, and finally 1000 μmol of δ-VL. The bottle was sealed and placed in a stable environment at 100 °C for polymerization reaction for 1 h under stirring.
[0222] (2) After the polymerization is completed, the pressure bottle is cooled to room temperature, dichloromethane is added to dissolve the obtained polymer to obtain a polymer solution, and then the polymer solution is uniformly poured into ethanol, filtered and vacuum dried to obtain PVL.
[0223] The polymerization time was 1 hour, the conversion rate of δ-VL monomer reached 99%, and the product (PVL) obtained above was subjected to GPC analysis and NMR analysis. The product obtained in Example 28 of the present invention was a polyester having a structure of Formula IV, with an actual molecular weight of 68.0 KDa and a molecular weight distribution of 1.42.
[0224] Embodiment 29
[0225] The catalyst used for PLLA in this embodiment is catalyst Al1.
[0226] The preparation method of PLLA in this embodiment comprises the following steps:
[0227] (1) In an inert atmosphere, 1 μmol of benzyl alcohol was added to a dry 15 mL pressure bottle, followed by 1 μmol of catalyst Al1, 1 mL of toluene, and stirred evenly. Finally, 100 μmol of L-LA was added, and the bottle was sealed and placed in a stable environment at 100°C for polymerization reaction for 6 h under stirring.
[0228] (2) After the polymerization is completed, the pressure bottle is cooled to room temperature, and the polymer solution is uniformly poured into ethanol (reverse precipitation), filtered and vacuum dried to obtain PLLA.
[0229] The polymerization time was 6h, and the conversion rate of L-LA monomer reached 98%. The above-obtained product (i.e., PLLA) was subjected to GPC analysis and NMR analysis. The product obtained in Example 29 of the present invention was a polyester having a structure of formula II-1, and its actual molecular weight was 16.2KDa. This example was to verify the solution polymerization of L-LA by the catalyst, monomer: catalyst: initiator = 100:1:1, the theoretical molecular weight was 14.4KDa, and the actual molecular weight reached 16.2KDa, indicating that the Al1 catalyst had good catalytic activity, and the polymerization was controllable, with a molecular weight distribution of 1.15.
[0230] Embodiment 30
[0231] The catalyst used for PCL in this embodiment is catalyst Al1.
[0232] The preparation method of PCL in this embodiment comprises the following steps:
[0233] (1) In an inert atmosphere, 1 μmol of benzyl alcohol was added to a dry 15 mL pressure bottle, followed by 1 μmol of catalyst Al1, 1 mL of toluene, and stirred evenly. Finally, 100 μmol of ε-CL was added, and the bottle was sealed and placed in a stable environment at 100 °C for polymerization reaction for 10 min under stirring.
[0234] (2) After the polymerization is completed, the pressure bottle is cooled to room temperature, and the polymer solution is uniformly poured into ethanol, filtered, and vacuum dried to obtain PCL.
[0235] The polymerization time was 10 min, the ε-CL monomer conversion rate reached 100%, and the catalytic activity of catalyst Al1 was higher than that of the catalyst reported in the literature. The above-obtained product (i.e. PCL) was subjected to GPC analysis and NMR analysis. The product obtained in Example 30 of the present invention was a polyester having a structure of formula III. This example was used to verify the solution polymerization of the catalyst for ε-CL. The monomer: catalyst: initiator = 100: 1: 1, the theoretical molecular weight was 11.4 KDa, and the actual molecular weight was 12.7 KDa, indicating that the Al1 catalyst had excellent catalytic activity for ε-CL, and the polymerization was controllable, with a molecular weight distribution of 1.11.
[0236] Embodiment 31
[0237] The catalyst used in the PVL of this embodiment is catalyst Al1.
[0238] The preparation method of PVL in this embodiment comprises the following steps:
[0239] (1) In an inert atmosphere, 1 μmol of benzyl alcohol was added to a dry 15 mL pressure bottle, followed by 1 μmol of catalyst Al1, 1 mL of toluene, and stirred evenly. Finally, 100 μmol of δ-VL was added, and the bottle was sealed and placed in a stable environment at 100°C for polymerization reaction for 20 min under stirring.
[0240] (2) After the polymerization is completed, the pressure bottle is cooled to room temperature, the polymer solution is uniformly poured into ethanol, filtered and vacuum dried to obtain PVL.
[0241] The polymerization time was 20 min, the δ-VL monomer conversion rate reached 100%, and the catalytic activity of catalyst Al1 was higher than that of the catalyst reported in the literature. The above-obtained product (i.e., PVL) was subjected to GPC analysis and NMR analysis. The product obtained in Example 31 of the present invention was a polyester having a structure of formula IV. This example was used to verify the solution polymerization of the catalyst for δ-VL. The monomer: catalyst: initiator = 100: 1: 1, the theoretical molecular weight was 10.0 KDa, and the actual molecular weight was 15.0 KDa, indicating that the Al1 catalyst had excellent catalytic activity for δ-VL, and the polymerization was controllable, with a molecular weight distribution of 1.19.
[0242] Embodiment 32
[0243] The catalyst used in the PLLA of this embodiment is a (AmPyPh)AlMe catalyst having a structure of formula Al2 (hereinafter referred to as "catalyst Al2"). The preparation method of PLLA in this embodiment includes the following steps:
[0244] (1) In an inert atmosphere, 1 μmol of benzyl alcohol was added to a dry 15 mL pressure bottle, followed by 1 μmol of catalyst Al2, and 1 mL of toluene was added and stirred evenly. Finally, 100 μmol of L-LA was added, and the mixture was sealed and placed in a stable environment at 100°C for polymerization reaction for 6 hours under stirring.
[0245] (2) After the polymerization is completed, the pressure bottle is cooled to room temperature, the polymer solution is uniformly poured into ethanol, filtered and vacuum dried to obtain PLLA.
[0246] The conversion rate of L-LA monomer reached 98% after 6 hours of polymerization. The above-obtained product (i.e., PLLA) was subjected to GPC analysis and NMR analysis. The product obtained in Example 32 of the present invention was a polyester having the structure of Formula II-1. This example was used to verify the solution polymerization of L-LA by the catalyst, with monomer: catalyst: initiator = 100: 1: 1, the theoretical molecular weight was 14.4 KDa, the actual molecular weight was 13.0 KDa, and the molecular weight distribution was 1.18.
[0247] Embodiment 33
[0248] The catalyst used in the PLLA of this embodiment is catalyst 12. The preparation method of PLLA in this embodiment includes the following steps:
[0249] (1) In an inert atmosphere, 1 μmol of benzyl alcohol was added to a dry 15 mL pressure bottle, followed by 1 μmol of catalyst Al2, and 1 mL of toluene was added and stirred evenly. Finally, 1000 μmol of L-LA was added, and the bottle was sealed and placed in a stable environment at 150°C for polymerization reaction for 16 hours under stirring.
[0250] (2) After the polymerization is completed, the pressure bottle is cooled to room temperature, the polymer solution is uniformly poured into ethanol, filtered and vacuum dried to obtain PLLA.
[0251] The polymerization time was 16 hours, and the conversion rate of L-LA monomer reached 91.0%. The above-obtained product (i.e., PLLA) was subjected to GPC analysis and NMR analysis. The product obtained in Example 33 of the present invention was a polyester having the structure of Formula II-1, with an actual molecular weight of 71.0 KDa and a molecular weight distribution of 1.51.
[0252] Embodiment 34
[0253] The catalyst used for PCL in this embodiment is catalyst Al2.
[0254] The preparation method of PCL in this embodiment comprises the following steps:
[0255] (1) In an inert atmosphere, 1 μmol of benzyl alcohol was added to a dry 15 mL pressure bottle, followed by 1 μmol of catalyst Al2, and finally 1000 μmol of ε-CL. The bottle was sealed and placed in a stable environment at 150°C for polymerization reaction for 1 hour under stirring.
[0256] (2) After the polymerization is completed, the pressure bottle is cooled to room temperature, and dichloromethane is added to dissolve the obtained polymer to obtain a polymer solution. The polymer solution is then uniformly poured into ethanol, filtered, and vacuum dried to obtain PCL.
[0257] The polymerization time was 1 hour, and the conversion rate of ε-CL monomer reached 97.0%. The above-obtained product (ie PCL) was subjected to GPC analysis and NMR analysis. The product obtained in Example 34 of the present invention was a polyester having a structure of Formula III, with an actual molecular weight of 125.0 KDa and a molecular weight distribution of 1.35.
[0258] Embodiment 35
[0259] The catalyst used in the PVL of this embodiment is catalyst Al2.
[0260] The preparation method of PVL in this embodiment comprises the following steps:
[0261] (1) In an inert atmosphere, 1 μmol of benzyl alcohol was added to a dry 15 mL pressure bottle, followed by 1 μmol of catalyst Al2, and finally 1000 μmol of δ-VL. The bottle was sealed and placed in a stable environment at 100 °C for polymerization reaction for 1 h under stirring.
[0262] (2) After the polymerization is completed, the pressure bottle is cooled to room temperature, dichloromethane is added to dissolve the obtained polymer to obtain a polymer solution, and then the polymer solution is uniformly poured into ethanol, filtered and vacuum dried to obtain PVL.
[0263] The polymerization time was 1 hour, and the conversion rate of δ-VL monomer reached 97.1%. The product (PVL) obtained above was subjected to GPC analysis and NMR analysis. The product obtained in Example 35 of the present invention was a polyester having a structure of Formula IV, with an actual molecular weight of 108.0 KDa and a molecular weight distribution of 1.41.
[0264] Embodiment 36
[0265] The catalyst used in the PLLA of this embodiment is a (AmPyPh)AlMe catalyst having a structure of formula Al3 (hereinafter referred to as "catalyst Al3"). The preparation method of PLLA in this embodiment includes the following steps:
[0266] (1) In an inert atmosphere, 1 μmol of benzyl alcohol was added to a dry 15 mL pressure bottle, followed by 1 μmol of catalyst Al3, and 1 mL of toluene was added and stirred evenly. Finally, 1000 μmol of L-LA was added, and the bottle was sealed and placed in a stable environment at 150°C for polymerization reaction for 16 hours under stirring.
[0267] (2) After the polymerization is completed, the pressure bottle is cooled to room temperature, dichloromethane is added to dissolve the obtained polymer to obtain a polymer solution, and then the polymer solution is uniformly poured into ethanol, filtered and vacuum dried to obtain PLLA.
[0268] The polymerization time was 16 hours, and the conversion rate of L-LA monomer reached 91.7%. The above product (i.e., PLLA) was subjected to GPC analysis and NMR analysis. The product obtained in Example 33 of the present invention was a polyester having the structure of Formula II-1, with an actual molecular weight of 69.7 KDa and a molecular weight distribution of 1.49.
[0269] Embodiment 37
[0270] The catalyst used for PCL in this embodiment is catalyst Al3.
[0271] The preparation method of PCL in this embodiment comprises the following steps:
[0272] (1) In an inert atmosphere, 1 μmol of benzyl alcohol was added to a dry 15 mL pressure bottle, followed by 1 μmol of catalyst Al3, and finally 1000 μmol of ε-CL. The bottle was sealed and placed in a stable environment at 150°C for polymerization reaction for 1 hour under stirring.
[0273] (2) After the polymerization is completed, the pressure bottle is cooled to room temperature, and dichloromethane is added to dissolve the obtained polymer to obtain a polymer solution. The polymer solution is then uniformly poured into ethanol, filtered, and vacuum dried to obtain PCL.
[0274] The polymerization time was 1 hour, and the conversion rate of ε-CL monomer reached 97.0%. The above-obtained product (ie PCL) was subjected to GPC analysis and NMR analysis. The product obtained in Example 37 of the present invention was a polyester having a structure of Formula III, with an actual molecular weight of 121.3 KDa and a molecular weight distribution of 1.41.
[0275] Embodiment 38
[0276] The catalyst used in the PVL of this embodiment is catalyst Al3.
[0277] The preparation method of PVL in this embodiment comprises the following steps:
[0278] (1) In an inert atmosphere, 1 μmol of benzyl alcohol was added to a dry 15 mL pressure bottle, followed by 1 μmol of catalyst Al3, and finally 1000 μmol of δ-VL. The bottle was sealed and placed in a stable environment at 100°C for polymerization reaction for 1 hour under stirring.
[0279] (2) After the polymerization is completed, the pressure bottle is cooled to room temperature, dichloromethane is added to dissolve the obtained polymer to obtain a polymer solution, and then the polymer solution is uniformly poured into ethanol, filtered and vacuum dried to obtain PVL.
[0280] The polymerization time was 1 hour, and the conversion rate of δ-VL monomer reached 97.1%. The product (PVL) obtained above was subjected to GPC analysis and NMR analysis. The product obtained in Example 38 of the present invention was a polyester having a structure of Formula IV, with an actual molecular weight of 98.0 KDa and a molecular weight distribution of 1.45.
[0281] Embodiment 39
[0282] The catalyst used in the PLLA of this embodiment is a (AmPyPh)AlMe catalyst having a structure of formula Al4 (hereinafter referred to as "catalyst Al4"). The preparation method of PLLA in this embodiment includes the following steps:
[0283] (1) In an inert atmosphere, 1 μmol of benzyl alcohol was added to a dry 15 mL pressure bottle, followed by 1 μmol of catalyst Al4, and 1 mL of toluene was added and stirred evenly. Finally, 1000 μmol of L-LA was added, and the bottle was sealed and placed in a stable environment at 150°C for polymerization reaction for 16 hours under stirring.
[0284] (2) After the polymerization is completed, the pressure bottle is cooled to room temperature, dichloromethane is added to dissolve the obtained polymer to obtain a polymer solution, and then the polymer solution is uniformly poured into ethanol, filtered and vacuum dried to obtain PLLA.
[0285] The polymerization time was 16 hours, and the conversion rate of L-LA monomer reached 81.3%. The above-obtained product (i.e., PLLA) was subjected to GPC analysis and NMR analysis. The product obtained in Example 39 of the present invention was a polyester having the structure of Formula II-1, with an actual molecular weight of 67.1 KDa and a molecular weight distribution of 1.51.
[0286] Embodiment 40
[0287] The catalyst used for PCL in this embodiment is catalyst Al4.
[0288] The preparation method of PCL in this embodiment comprises the following steps:
[0289] (1) In an inert atmosphere, 1 μmol of benzyl alcohol was added to a dry 15 mL pressure bottle, followed by 1 μmol of catalyst Al4 and finally 1000 μmol of ε-CL. The bottle was sealed and placed in a stable environment at 150°C for polymerization reaction for 1 hour under stirring.
[0290] (2) After the polymerization is completed, the pressure bottle is cooled to room temperature, and dichloromethane is added to dissolve the obtained polymer to obtain a polymer solution. The polymer solution is then uniformly poured into ethanol, filtered, and vacuum dried to obtain PCL.
[0291] The polymerization time was 1 hour, and the conversion rate of ε-CL monomer reached 97.0%. The above-obtained product (ie PCL) was subjected to GPC analysis and NMR analysis. The product obtained in Example 40 of the present invention was a polyester having a structure of Formula III, with an actual molecular weight of 111.5 KDa and a molecular weight distribution of 1.43.
[0292] Embodiment 41
[0293] The catalyst used in the PVL of this embodiment is catalyst Al4.
[0294] The preparation method of PVL in this embodiment comprises the following steps:
[0295] (1) In an inert atmosphere, 1 μmol of benzyl alcohol was added to a dry 15 mL pressure bottle, followed by 1 μmol of catalyst Al4, and finally 1000 μmol of δ-VL. The bottle was sealed and placed in a stable environment at 100 °C for polymerization reaction for 1 h under stirring.
[0296] (2) After the polymerization is completed, the pressure bottle is cooled to room temperature, dichloromethane is added to dissolve the obtained polymer to obtain a polymer solution, and then the polymer solution is uniformly poured into ethanol, filtered and vacuum dried to obtain PVL.
[0297] The polymerization time was 1 hour, and the conversion rate of δ-VL monomer reached 91.2%. The product (PVL) obtained above was subjected to GPC analysis and NMR analysis. The product obtained in Example 41 of the present invention was a polyester having a structure of Formula IV, with an actual molecular weight of 108.0 KDa and a molecular weight distribution of 1.43.
[0298] Embodiment 42
[0299] The catalyst used in the PLLA of this embodiment is a (AmPyPh)AlMe catalyst having a structure of formula Al5 (hereinafter referred to as "catalyst Al5"). The preparation method of PLLA in this embodiment includes the following steps:
[0300] (1) In an inert atmosphere, 1 μmol of benzyl alcohol was added to a dry 15 mL pressure bottle, followed by 1 μmol of catalyst Al5, and 1 mL of toluene was added and stirred evenly. Finally, 1000 μmol of L-LA was added, and the bottle was sealed and placed in a stable environment at 150°C for polymerization reaction for 16 hours under stirring.
[0301] (2) After the polymerization is completed, the pressure bottle is cooled to room temperature, dichloromethane is added to dissolve the obtained polymer to obtain a polymer solution, and then the polymer solution is uniformly poured into ethanol, filtered and vacuum dried to obtain PLLA.
[0302] The polymerization time was 16 hours, and the conversion rate of L-LA monomer reached 85.0%. The above-obtained product (i.e., PLLA) was subjected to GPC analysis and NMR analysis. The product obtained in Example 35 of the present invention was a polyester having the structure of Formula II-1, with an actual molecular weight of 70.2 KDa and a molecular weight distribution of 1.53.
[0303] Embodiment 43
[0304] The catalyst used for PCL in this embodiment is catalyst Al5.
[0305] The preparation method of PCL in this embodiment comprises the following steps:
[0306] (1) In an inert atmosphere, 1 μmol of benzyl alcohol was added to a dry 15 mL pressure bottle, followed by 1 μmol of catalyst Al5 and finally 1000 μmol of ε-CL. The bottle was sealed and placed in a stable environment at 150°C for polymerization reaction for 1 hour under stirring.
[0307] (2) After the polymerization is completed, the pressure bottle is cooled to room temperature, and dichloromethane is added to dissolve the obtained polymer to obtain a polymer solution. The polymer solution is then uniformly poured into ethanol, filtered, and vacuum dried to obtain PCL.
[0308] The polymerization time was 1 hour, and the conversion rate of ε-CL monomer reached 92.0%. The above-obtained product (ie PCL) was subjected to GPC analysis and NMR analysis. The product obtained in Example 43 of the present invention was a polyester having a structure of Formula III, with an actual molecular weight of 117.3 KDa and a molecular weight distribution of 1.41.
[0309] Embodiment 44
[0310] The catalyst used in the PVL of this embodiment is catalyst Al5.
[0311] The preparation method of PVL in this embodiment comprises the following steps:
[0312] (1) In an inert atmosphere, 1 μmol of benzyl alcohol was added to a dry 15 mL pressure bottle, followed by 1 μmol of catalyst Al5, and finally 1000 μmol of δ-VL. The bottle was sealed and placed in a stable environment at 100°C for polymerization reaction for 1 hour under stirring.
[0313] (2) After the polymerization is completed, the pressure bottle is cooled to room temperature, dichloromethane is added to dissolve the obtained polymer to obtain a polymer solution, and then the polymer solution is uniformly poured into ethanol, filtered and vacuum dried to obtain PVL.
[0314] The polymerization time was 1 hour, and the conversion rate of δ-VL monomer reached 90.0%. The product (PVL) obtained above was subjected to GPC analysis and NMR analysis. The product obtained in Example 44 of the present invention was a polyester having a structure of Formula IV, with an actual molecular weight of 98.0 KDa and a molecular weight distribution of 1.43.
[0315] Embodiment 45
[0316] The catalyst used in the PLLA of this embodiment is a (AmPyPh)AlMe catalyst having a structure of formula Al6 (hereinafter referred to as "catalyst Al6"). The preparation method of PLLA in this embodiment includes the following steps:
[0317] (1) In an inert atmosphere, 1 μmol of benzyl alcohol was added to a dry 15 mL pressure bottle, followed by 1 μmol of catalyst Al6, and 1 mL of toluene was added and stirred evenly. Finally, 1000 μmol of L-LA was added, and the bottle was sealed and placed in a stable environment at 150°C for polymerization reaction for 16 hours under stirring.
[0318] (2) After the polymerization is completed, the pressure bottle is cooled to room temperature, dichloromethane is added to dissolve the obtained polymer to obtain a polymer solution, and then the polymer solution is uniformly poured into ethanol, filtered and vacuum dried to obtain PLLA.
[0319] The polymerization time was 16 hours, and the conversion rate of L-LA monomer reached 72.0%. The above product (i.e., PLLA) was subjected to GPC analysis and NMR analysis. The product obtained in Example 45 of the present invention was a polyester having the structure of Formula II-1, with an actual molecular weight of 64.2 KDa and a molecular weight distribution of 1.51.
[0320] Embodiment 46
[0321] The catalyst used for PCL in this embodiment is catalyst Al6.
[0322] The preparation method of PCL in this embodiment comprises the following steps:
[0323] (1) In an inert atmosphere, 1 μmol of benzyl alcohol was added to a dry 15 mL pressure bottle, followed by 1 μmol of catalyst Al6, and finally 1000 μmol of ε-CL. The bottle was sealed and placed in a stable environment at 150°C for polymerization reaction for 1 hour under stirring.
[0324] (2) After the polymerization is completed, the pressure bottle is cooled to room temperature, and dichloromethane is added to dissolve the obtained polymer to obtain a polymer solution. The polymer solution is then uniformly poured into ethanol, filtered, and vacuum dried to obtain PCL.
[0325] The polymerization time was 1 hour, and the conversion rate of ε-CL monomer reached 97.0%. The above-obtained product (ie PCL) was subjected to GPC analysis and NMR analysis. The product obtained in Example 46 of the present invention was a polyester having a structure of Formula III, with an actual molecular weight of 121.3 KDa and a molecular weight distribution of 1.42.
[0326] Embodiment 47
[0327] The catalyst used in the PVL of this embodiment is catalyst Al6.
[0328] The preparation method of PVL in this embodiment comprises the following steps:
[0329] (1) In an inert atmosphere, 1 μmol of benzyl alcohol was added to a dry 15 mL pressure bottle, followed by 1 μmol of catalyst Al6, and finally 1000 μmol of δ-VL. The bottle was sealed and placed in a stable environment at 100 °C for polymerization reaction for 1 h under stirring.
[0330] (2) After the polymerization is completed, the pressure bottle is cooled to room temperature, dichloromethane is added to dissolve the obtained polymer to obtain a polymer solution, and then the polymer solution is uniformly poured into ethanol, filtered and vacuum dried to obtain PVL.
[0331] The polymerization time was 1 hour, and the conversion rate of δ-VL monomer reached 90.0%. The product (PVL) obtained above was subjected to GPC analysis and NMR analysis. The product obtained in Example 47 of the present invention was a polyester having a structure of Formula IV, with an actual molecular weight of 98.0 KDa and a molecular weight distribution of 1.45.
[0332] Embodiment 48
[0333] The catalyst used for PLLA in this embodiment is (AmPyPh)AlMe catalyst having a structure of formula Al7 (hereinafter referred to as "catalyst Al7"). The preparation method of PLLA in this embodiment includes the following steps:
[0334] (1) In an inert atmosphere, 1 μmol of benzyl alcohol was added to a dry 15 mL pressure bottle, followed by 1 μmol of catalyst Al7, and 1 mL of toluene was added and stirred evenly. Finally, 1000 μmol of L-LA was added, and the bottle was sealed and placed in a stable environment at 150°C for polymerization reaction for 2 h under stirring.
[0335] (2) After the polymerization is completed, the pressure bottle is cooled to room temperature, dichloromethane is added to dissolve the obtained polymer to obtain a polymer solution, and then the polymer solution is uniformly poured into ethanol, filtered and vacuum dried to obtain PLLA.
[0336] The polymerization time was 2 hours, and the conversion rate of L-LA monomer reached 91.0%. The above product (i.e., PLLA) was subjected to GPC analysis and NMR analysis. The product obtained in Example 48 of the present invention was a polyester having the structure of Formula II-1, with an actual molecular weight of 54.3 KDa and a molecular weight distribution of 1.39.
[0337] Embodiment 49
[0338] The catalyst used for PCL in this embodiment is catalyst Al7.
[0339] The preparation method of PCL in this embodiment comprises the following steps:
[0340] (1) In an inert atmosphere, 1 μmol of benzyl alcohol was added to a dry 15 mL pressure bottle, followed by 1 μmol of catalyst Al7, and finally 1000 μmol of ε-CL. The bottle was sealed and placed in a stable environment at 150°C for polymerization reaction for 0.5 h under stirring.
[0341] (2) After the polymerization is completed, the pressure bottle is cooled to room temperature, and dichloromethane is added to dissolve the obtained polymer to obtain a polymer solution. The polymer solution is then uniformly poured into ethanol, filtered, and vacuum dried to obtain PCL.
[0342] The polymerization time was 0.5 h, and the conversion rate of ε-CL monomer reached 99.0%. The above-obtained product (ie PCL) was subjected to GPC analysis and NMR analysis. The product obtained in Example 49 of the present invention was a polyester having a structure of Formula III, with an actual molecular weight of 127.3 KDa and a molecular weight distribution of 1.32.
[0343] Embodiment 50
[0344] The catalyst used in the PVL of this embodiment is catalyst Al7.
[0345] The preparation method of PVL in this embodiment comprises the following steps:
[0346] (1) In an inert atmosphere, 1 μmol of benzyl alcohol was added to a dry 15 mL pressure bottle, followed by 1 μmol of catalyst Al7, and finally 1000 μmol of δ-VL. The bottle was sealed and placed in a stable environment at 100°C for polymerization reaction for 0.5 h under stirring.
[0347] (2) After the polymerization is completed, the pressure bottle is cooled to room temperature, dichloromethane is added to dissolve the obtained polymer to obtain a polymer solution, and then the polymer solution is uniformly poured into ethanol, filtered and vacuum dried to obtain PVL.
[0348] The polymerization time was 0.5 h, the conversion rate of δ-VL monomer reached 99.0%, and the product (PVL) obtained was subjected to GPC analysis and NMR analysis. The product obtained in Example 50 of the present invention is a polyester having a structure of Formula IV, with an actual molecular weight of 104.3 KDa and a molecular weight distribution of 1.37.
[0349] Embodiment 51
[0350] The catalyst used in the PLLA of this embodiment is a (AmPyPh)AlMe catalyst having a structure of formula Al8 (hereinafter referred to as "catalyst Al8"). The preparation method of PLLA in this embodiment includes the following steps:
[0351] (1) In an inert atmosphere, 1 μmol of benzyl alcohol was added to a dry 15 mL pressure bottle, followed by 1 μmol of catalyst Al8, and 1 mL of toluene was added and stirred evenly. Finally, 1000 μmol of L-LA was added, and the bottle was sealed and placed in a stable environment at 150°C for polymerization reaction for 2 h under stirring.
[0352] (2) After the polymerization is completed, the pressure bottle is cooled to room temperature, dichloromethane is added to dissolve the obtained polymer to obtain a polymer solution, and then the polymer solution is uniformly poured into ethanol, filtered and vacuum dried to obtain PLLA.
[0353] The polymerization time was 2 hours, and the conversion rate of L-LA monomer reached 91.7%. The above-obtained product (i.e., PLLA) was subjected to GPC analysis and NMR analysis. The product obtained in Example 51 of the present invention was a polyester having the structure of Formula II-1, with an actual molecular weight of 55.8 KDa and a molecular weight distribution of 1.40.
[0354] Embodiment 52
[0355] The catalyst used for PCL in this embodiment is catalyst Al8.
[0356] The preparation method of PCL in this embodiment comprises the following steps:
[0357] (1) In an inert atmosphere, 1 μmol of benzyl alcohol was added to a dry 15 mL pressure bottle, followed by 1 μmol of catalyst Al8, and finally 1000 μmol of ε-CL. The bottle was sealed and placed in a stable environment at 150°C for polymerization reaction for 0.5 h under stirring.
[0358] (2) After the polymerization is completed, the pressure bottle is cooled to room temperature, and dichloromethane is added to dissolve the obtained polymer to obtain a polymer solution. The polymer solution is then uniformly poured into ethanol, filtered, and vacuum dried to obtain PCL.
[0359] The polymerization time was 0.5 h, and the conversion rate of ε-CL monomer reached 99.0%. The above-obtained product (ie PCL) was subjected to GPC analysis and NMR analysis. The product obtained in Example 52 of the present invention was a polyester having a structure of Formula III, with an actual molecular weight of 137.3 KDa and a molecular weight distribution of 1.37.
[0360] Embodiment 53
[0361] The catalyst used in the PVL of this embodiment is catalyst Al8.
[0362] The preparation method of PVL in this embodiment comprises the following steps:
[0363] (1) In an inert atmosphere, 1 μmol of benzyl alcohol was added to a dry 15 mL pressure bottle, followed by 1 μmol of catalyst Al8, and finally 1000 μmol of δ-VL. The bottle was sealed and placed in a stable environment at 100°C for polymerization reaction for 0.5 h under stirring.
[0364] (2) After the polymerization is completed, the pressure bottle is cooled to room temperature, dichloromethane is added to dissolve the obtained polymer to obtain a polymer solution, and then the polymer solution is uniformly poured into ethanol, filtered and vacuum dried to obtain PVL.
[0365] The polymerization time was 0.5 h, the conversion rate of δ-VL monomer reached 99.0%, and the product (PVL) obtained was subjected to GPC analysis and NMR analysis. The product obtained in Example 53 of the present invention was a polyester having a structure of Formula IV, with an actual molecular weight of 102.3 KDa and a molecular weight distribution of 1.34.
[0366] From the above content, it can be seen that the (AmPyPh)AlMe catalyst of the present invention can catalyze the ring-opening homopolymerization of lactide (L-LA or rac-LA), ε-caprolactone (ε-CL) and δ-valerolactone (δ-VL) to produce polylactic acid (PLA), polycaprolactone (PCL) and polyvalerolactone (PVL).
[0367] The description of the above embodiments is only used to help understand the method of the present invention and its core idea. It should be noted that for those of ordinary skill in the art, without departing from the principles of the present invention, several improvements and modifications may be made to the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention. The various modifications to these embodiments are obvious to those skilled in the art, and the general principles defined in the present invention may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to these embodiments of the present invention, but will conform to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. An aniline pyridine amino-aluminum catalyst, characterized in that Selected from Al1-Al9 structure complexes:
2. A method for preparing the anilinopyridine amino-aluminum catalyst according to claim 1, characterized in that: The following steps are involved: The aniline pyridine amino ligand is dissolved in a pressure-resistant bottle filled with a good solvent, an aluminum source is added dropwise, and the mixture is sealed and heated to 100 to 105° C. for reaction for 16 to 30 hours. After the reaction is completed, the solvent is drained and recrystallized using ultra-dry n-hexane to obtain the aniline pyridine amino-aluminum catalyst; The anilinopyridineamino ligand is selected from compounds of any structure from LA to LI:
3. The method for preparing the anilinopyridine amino-aluminum catalyst according to claim 2, characterized in that: The aluminum source is trimethylaluminum; the good solvent for dissolving the anilinopyridine amino ligand is tetrahydrofuran, dichloromethane or toluene; the good solvent for dissolving the aluminum source is toluene or n-hexane.
4. Use of the anilinopyridineamino-aluminum catalyst according to claim 1 in catalyzing the ring-opening polymerization of lactide and / or lactone.
5. A method for catalyzing the ring-opening polymerization of lactide and / or lactone using the anilinopyridineamino-aluminum catalyst according to claim 1, characterized in that: The method comprises the following steps: mixing lactide and / or lactone monomers, anilinopyridine amino-aluminum catalyst and an initiator, carrying out polymerization reaction at a temperature of 150-160 DEG C, dissolving the obtained polymer after the polymerization reaction, and drying after reverse precipitation.
Citation Information
Patent Citations
Catalyst compounds and use thereof
CN101896507A
Cited By
High-strength degradable ultralow-temperature-resistant polyester adhesive and preparation method thereof
CN120365878A
High-strength degradable ultra-low temperature resistant polyester adhesive and preparation method thereof
CN120365878B
Pyridine amine phenol zinc catalyst and preparation method and application thereof
CN121045223A
A pyridine amine zinc catalyst, a preparation method and application thereof
CN121045223B